2020
DOI: 10.3892/ijmm.2020.4637
|View full text |Cite|
|
Sign up to set email alerts
|

Rotenone restrains colon cancer cell viability, motility and epithelial‑mesenchymal transition and tumorigenesis in nude mice via the PI3K/AKT pathway

Abstract: Rotenone, a natural hydrophobic pesticide, has been reported to display anticancer activity in a variety of cancer cells. However, the mechanism of rotenone on colon cancer (cc) cell migration, invasion and metastasis is still unknown. In the present study, the cytotoxicity of rotenone on cc cells were detected by the cell counting Kit-8 assay and confirmed by clone formation assay. The effects of rotenone on cc cell invasion and migration activity were determined in vitro by Transwell invasion and wound heali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…It is mainly used as a pesticide in agriculture and aquaculture, but its use has raised major concern because of its off-target effects on other species in the agricultural field and aquatic ecosystem (Heinz et al 2017). In human biology, it exhibits promising anticancer properties (Xiao et al 2020), but in our study, we found that it showed significant toxicity to non-cancer cells. Previous studies have shown that MTZ and 8-OAc similarly exhibit significant activity against a wide range of cancer cell types (Johnson et al 2020).…”
Section: Discussionmentioning
confidence: 68%
“…It is mainly used as a pesticide in agriculture and aquaculture, but its use has raised major concern because of its off-target effects on other species in the agricultural field and aquatic ecosystem (Heinz et al 2017). In human biology, it exhibits promising anticancer properties (Xiao et al 2020), but in our study, we found that it showed significant toxicity to non-cancer cells. Previous studies have shown that MTZ and 8-OAc similarly exhibit significant activity against a wide range of cancer cell types (Johnson et al 2020).…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, Chelidonine and Rotenone, whose anti-tumor potential has been evaluated also in recent reports [51,52], were found to produce a potent anticancer activity mediated by their capability to bind and stabilize telomeric G4 structures. In particular, demonstrating that both compounds are effective at low µM doses and show selectivity for tumor cells, our results pave the way for the design of novel and even more effective synthetic analogs of these natural compounds that could find their application field in anticancer therapies.…”
Section: Discussionmentioning
confidence: 94%
“…Hence, it could be hypothesized that kaempferol may also be useful for conditions characterized by dysregulated autophagy, such as HIV-associated neurodegenerative diseases. Additionally, it also can be assumed that kaempferol may be effective against diseases characterized by abnormal activation of the PIK3/Akt/mTOR pathway that benefit from mTOR inhibitors, including infectious diseases, such as HIV and severe acute respiratory syndrome coronavirus 2 ( 41 43 ), and autoimmune diseases, such as multiple sclerosis and systemic lupus erythematosus ( 44 46 ), as well as cancer ( 47 49 ).…”
Section: Discussionmentioning
confidence: 99%